Closing the Gender Gap: Gender Based Taxation, Wage Subsidies or Basic Income? - Ugo Colombino; Edlira Narazani (European Commission, Joint Research Centre (JRC), 2018)
Gender based taxation (GBT) has been recently proposed as a promising policy in order to close the gender gap, i.e. promote gender equality and improve women's status in the labour market and within the family. We use a microeconometric model of household labour supply in order to evaluate, with Italian data, the behavioural and welfare effects of GBT as compared to other policies based on different optimal taxation principles. The comparison is interesting because GBT, although technically correct, might face implementation difficulties not shared by other policies that in turn might produce comparable benefits. Our results support to some extent the expectations of GBT's proponents. However, it is not an unquestionable success. GBT induces a modest increase of women's employment, but similar effects can be attained by universal subsidies on low wages. When the policies are evaluated in terms of welfare, GBT ranks first among single women but among couples and in the whole population the best policies are unconditional transfers and/or subsidies on low wages.
Keywords: 330; Gender based taxation; wage subsidies; basic income; guaranteed minimum income; labour supply; social welfare